Assessing atrial fibrillation–related quality of life improvements one year after ablation: A systematic review and meta‐analysis. - Yergeshov, Kanat; Kulzhanov, Maksut; Abdrakhmanov, Ayan; Ramazanov, Manas; Anartayev, Saken (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: This systematic review and meta-analysis quantify the magnitude of change in overall and domain-specific health-related quality of life  (HRQoL) following atrial fibrillation (AF) ablation and evaluate the consistency of these improvements across different study designs.Methods: A systematic search was conducted in four electronic databases: PubMed, Scopus, Web of Science, ScienceDirect, and Google Scholar, using a standard search strategy. Mean differences in Atrial Fibrillation Effect on Quality-of-Life (AFEQT) questionnaire with 95 % confidence intervals were calculated in R using meta and metafor packages.Results: Our meta-analysis of 14 studies involving 25,507 patients demonstrates that AF ablation yields substantial and clinically meaningful quality‐of‐life gains at 12 months: the pooled overall AFEQT score improved by 25.7 points (21.7–29.6), with domain‐specific increases of 23.6 points in symptoms (19.1–28.0); 28.2 points in daily activities (24.0–32.5), 23.6 points in treatment concern (19.2–28.0), and 24.9 points in treatment satisfaction (18.9–31.0).Conclusions: AF ablation yields large, clinically meaningful HRQoL improvements across all AFEQT domains. Routine integration of AFEQT monitoring into clinical pathways is warranted. Future studies should standardize protocols, extend follow-up beyond one year, and target domains with smaller gains to sustain benefits.